Presidential Decree-Law No. 12 of the Year 2015 Amending Some Provisions of the General Sales Tax Law Promulgated by Law No. 11 of the Year 1991 = قرار رئيس جمهورية مصر العربية بالقانون رقم 12 لسنة 2015 بتعديل بعض أحكام قانون الضريبة العامة على المبيعات الصادر بالقانون رقم 11 لسنة 1991 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic